Heart failure disease management program, its contribution to established pharmacotherapy and long-term prognosis in real clinical practice - retrospective data analysis - Lazarova, Marie; Lazar, Dusan; Malek, Filip; Vaclavik, Jan; Taborsky, Milos; Ignaszewski, Andrew (Biomedical papers, 2019)
Background and Aims: The prognosis of patients with heart failure (HF) is still generally unfavorable. HF with reduced ejection fraction (HFrEF) patients reach target medication doses in very low percentages in daily clinical practice. HF disease management programs (DMP), including nurse and telemedicine support that facilitate achieving target medication doses, may improve the unfavorable prognosis. Methods: We retrospectively analyzed the data of 738 patients with HFrEF who were followed in a single HF center during the years 1975-2011, for 6.4 (median) years. DMP, nurse and telemedicine support is established at this center. Results: The group achieved left ventricle (LV) recovery after the HF treatment. The median LV ejection fraction improved from 25.0% at baseline to 50.0% at the time of the latest data collection. The proportion of NYHA II, III and IV classes decreased from 27.6%, 30.2% and 29.7% to 26.6%, 7.2% and 0.1%, respectively while the proportion of NYHA class I increased from 12.5% to 66.1%. Median NT-proBNP decreased from 975.0 to 324.0 pg/mL. The survival of the patient group was favorable; 79.7% survived 18.1 years after diagnosis of HF. A high percentage of the patients received recommended target or higher than target doses of angiotensin-converting enzyme inhibitors (82.0%) and beta-blockers (78.1%). Conclusion: The established pharmacotherapy resulted from an effective DMP and this contributed to the favorable prognosis.
Keywords: disease management program; heart failure; long term prognosis; pharmacotherapy dose